Repeated intra‐articular injections of acidic saline produce long‐lasting joint pain and widespread hyperalgesia. (27th August 2014) - Sugimura, N.; Ikeuchi, M.; Izumi, M.; Kawano, T.; Aso, K.; Kato, T.; Ushida, T.; Yokoyama, M.; Tani, T.
Abstract Background Synovial fluid in inflamed joint shows a drop in pH, which activates proton‐gated ion channels in nociceptors. No studies have ever tried to develop and characterize acid‐induced joint pain. Methods Rats were injected intra‐articularly with pH 4.0 acidic saline twice, 5 days apart. Pain‐related behaviour tests including weight‐bearing asymmetry, paw withdrawal threshold and knee compression threshold were conducted. To clarify the roles of proton‐gated ion channels, rats were injected intra‐articularly with selective antagonists for ASIC1a, ASIC3 and TRPV1 on day 5 (before the second injection) or on day 14. Underlying peripheral and central pain mechanisms were evaluated using joint histology, interleukin‐1β concentrations in the synovium, single‐fibre recording of the knee afferent and expression of phosphorylated cyclic adenosine monophosphate‐responsive element‐binding protein (p‐CREB) in the spinal dorsal horn. Results Repeated injections of acidic saline induced weight‐bearing asymmetry, decrease in paw withdrawal threshold and knee compression threshold bilaterally, which lasted until day 28. Early administration of ASIC3 antagonist reduced the bilateral and long‐lasting hyperalgesia. Neither articular degeneration nor synovial inflammation was observed. C‐fibre of the knee afferent was activated by acidic saline, which was attenuated by pre‐injection of ASIC3 antagonist. p‐CREB expression was transiently up‐regulated bilaterally on day 6, but not on day 14. Conclusion We developed and characterized a model of acid‐induced long‐lasting bilateral joint pain. Peripheral ASIC3 and spinal p‐CREB played important roles for the development of hyperalgesia. This animal model gives insights into the mechanisms of joint pain, which is helpful in developing better pain treatments.